Effects of Wetland Reclamation on Soil Nutrient Losses and Reserves in Sanjiang Plain, Northeast China - Yang WANG; Jing-shuang LIU; Jin-da WANG; Chong-yu SUN (Journal of Integrative Agriculture, 2012)
The carbon (C), nitrogen (N) and phosphorus (P) variations of a temperate wetland soil under continuous cultivation for 40 yr were determined and evaluated in the Sanjiang Plain, Northeast China. The results showed that the soil organic carbon (SOC) and total nitrogen (TN) contents in each soil layer decreased sharply after cultivation for 2-3 yr, and exhibited minor differences after cultivation for 11 yr, which showed an exponential decline curve with the increase of cultivation years. The reduction rates of carbon and nitrogen reserves were 14.79% and 28.53% yr−1 at the initial reclamation stages of 2-3 yr and then decreased to 2.02-3.08% yr−1 and 1.98-2.93% yr−1 after cultivation for 20 yr, respectively. Soil total phosphorus (TP) reserves decreased within cultivation for 5 yr, and then gradually restored to the initial level after cultivation for 17 yr. Both SOC and TN could be restored slightly when the farmland was left fallow for 8 yr after reclamation for 11 yr, whereas TP had no significant difference. These results demonstrated that wetland cultivation was one of the most important factors influencing on the nutrient fate and reserves in soil, which could lead to the rapid nutrient release and slow restoration through abandon cultivation, therefore protective cultivation techniques preventing nutrients from loss should be immediately established after wetland reclamation.